Mongolian camel caravans culture - D. Urnukhdelger (Nomadic Civilization: Historical Research, 2021)
This article describes the history and traditions of Mongolian nomads transporting camels over long distances, the culture and methods of camel caravans that are unique to other countries and nations, the rituals, language, and unique features of camel caravans. Camel caravan, which has been one of the rhythms and meanings of the ancient life of Mongolians, has a rich history, customs and heritage for many years. Mongolians have a long tradition of riding camels, loading their backs, and riding in sleighs. Until recently, camels were widely used in Mongolia for the development of road transport and railways, as well as for the transportation of goods needed by the country and the people. Camels are still the main source of transportation for local herders. Mongolians have a long tradition of riding camels, loading their backs, and riding in sleighs as draught animal, and transportation. Until recently, camels were widely used in Mongolia for the weak development of road transport and railways. Camels widely used for the transportation of goods and goods needed by the country and the people, as well as for the movement of herders. Even today, camels are mainly used for daily transportation and transportation of local herder. History has shown that camels and camel caravan were the mainstays of the trade or Silk Road connecting Asia and Europe. The Mongol Empire during the reign of Genghis Khan played an important role in the development of this Silk Road, and in the 13th century the so-called “Ministry of Camel of burden” was established in Mongolia. The Ministry of Camels was established because camels played a key role in carrying long distances, loading weapons in war, and transporting booty. During the Great Mongol Empire, the eastern branch of the Silk Road passed through Kharkhorum. The Silk Road connected Central Asia, Mongolia, China, and India with the Middle East and later Europe, and played an important role in establishing contacts, trade, and civilization among the committees of these countries. The length of the Silk Road was more than 7,000 km. and most of this road was traveled by camels. Since the advent of the Silk Road, Mongolian nomads have developed a sophisticated method of camel weighing that is unique to any other country or nation. In fact, for centuries, camels were the only means of transportation for trade and commerce within the country and with neighboring nations. Camels moved from any province of Mongolia to the capital, Uliastai, Khovd, Sanbees, Khiagt, Zaya Shavig, and Wang Khuree, as well as to Beijing, China, Chuulalt-Gate, Hohhot, Manchuria, Hailar, and Dolon Lake, Tsonj, Bar Khul, Urumch, Gunchen, Zhanchkhuu, Biysk, Khosh-Agach, and Troitskosavsk, Russia supplying with wool, hides, fur, ﬂour, rice, tea, and daalimba (cotton).